Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen (Studi Kasus pada Bank BRI Capem Polban) - Onata, Ivano; Mukaram (Applied Business and Administration Journal, 2023)
This study used the descriptive analysis method. The activities carried out are data analysis and distribution of questionnaires. The number of respondents was collected by as many as 115 people. Of the 115 respondents, the population of this study are customers of Bank BRI or have ever transacted at BRI bank. The statistical analysis used is regression analysis using the SPSS version 22 application. The results of this study indicate that the service quality is satisfied based on the mean value of 4.06. The results of the data analysis show that the mean value of consumer satisfaction is 3.87. This value indicates that the level of consumer satisfaction is sufficient to be satisfied. The regression coefficient shows that service quality influence 0.304 to customer satisfaction with a significance level of 0.000. Thus, it can be concluded that service quality has a significant effect on customer satisfaction.